A methodology for flipped learning in a cloud-oriented environment: enhancing future IT specialists' training - Olena G. Glazunova; Valentyna I. Korolchuk; Oleksandra V. Parhomenko; Tetiana V. Voloshyna; Natalia V. Morze; Eugenia M. Smyrnova-Trybulska (Academy of Cognitive and Natural Sciences, 2023)
The article discusses the components of a cloud-oriented environment for flipped learning in higher education institutions. It presents a methodology that utilizes various services and resources available in the university's cloud-oriented environment. The methodology is divided into three stages: preparatory, basic, and integrated. During the preparatory stage, students collaborate on collective projects within one discipline using Microsoft Teams. The aim is to develop general competencies. At the basic stage, students engage in tasks such as mini-projects, group projects, and individual projects while studying professionally-oriented disciplines. These tasks are performed using the GitHub cloud service. The integrated stage involves working on interdisciplinary projects that draw from multiple disciplines. The tasks for these projects are formed based on the study of several disciplines and utilize the Jira service. The article investigates the effectiveness of this methodology for flipped learning by analyzing its application in the university's cloud-oriented environment.